2016
DOI: 10.1590/2318-0331.011615010
|View full text |Cite
|
Sign up to set email alerts
|

Variação da qualidade da água de chuva com a precipitação: aplicação à cidade de Santa Maria - RS

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado. Variação da qualidade da água de chuva com a precipitação: aplicação à cidade de Santa Maria -RSVariation of rainwater quality with precipitation: application to Santa Maria city -RS RESUMOEste trabalho avaliou a qualidade da água da chuva na cidade de Santa Maria -RS, a variação… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
(10 reference statements)
1
5
0
8
Order By: Relevance
“…The mean Mn values in the wet season were 0.04 ± 0.02 mg L -1 for DP, 0.60 ± 0.78 mg L -1 for FF and 0.04 ± 0.03 mg L -1 for RR. A similar concentration of Mn in wet deposition was found in rainwater samples in Santa Maria, Rio Grande do Sul and Greece (Hagemann and Gastaldini, 2016;Melidis et al, 2007). In the dry season, only the samples of May 2018 were below the limit of quantification (LQ).…”
Section: Metalsupporting
confidence: 60%
See 1 more Smart Citation
“…The mean Mn values in the wet season were 0.04 ± 0.02 mg L -1 for DP, 0.60 ± 0.78 mg L -1 for FF and 0.04 ± 0.03 mg L -1 for RR. A similar concentration of Mn in wet deposition was found in rainwater samples in Santa Maria, Rio Grande do Sul and Greece (Hagemann and Gastaldini, 2016;Melidis et al, 2007). In the dry season, only the samples of May 2018 were below the limit of quantification (LQ).…”
Section: Metalsupporting
confidence: 60%
“…In the humid period, there is a greater variation in pH than in the dry period; in addition, the rain is more acidic in the less rainy period, as has also been confirmed by research on rainwater in Minas Gerais (Cerqueira et al, 2014). The highest pH values are found at the points where the water traveled through the roof (FF and RR), possibly as a result of the deposition of dissolved solids (Hagemann and Gastaldini, 2016). The feces of birds that are considered to be alkaline and have a high concentration of NH3 lead to an increase in pH at the points of total deposition.…”
Section: Physico-chemical Parametersmentioning
confidence: 56%
“…The median pH values for the points CA 01, CT 01, OA 06 and OT 061º were practically the same, all of which meet the recommended by NBR 15527 (ABNT, 2007). Hagemann and Gastaldini (2016) also observed that the pH values of rainwater samples collected from the roof were within the established by the norm.…”
Section: Variation In the Quality Of Rainwater After Passing Through mentioning
confidence: 60%
“…The volume of the collectors was 4.0 L, in order to guarantee that the water would not overflow during a rain. These collectors were cleaned before a rainy event to avoid possible changes in the characteristics of the collected water, as recommended by Hagemann and Gastaldini (2016). In order to check the possibility of rainwater contamination by the material that constitutes the plastic collector, a water quality test was carried out for all collectors.…”
Section: Spatial-temporal Variation In Rainwater Quality and Complianmentioning
confidence: 99%
See 1 more Smart Citation